PENENTUAN MINAT BACA SISWA DALAM PEMINJAMAN BUKU DENGAN METODE SMART (SIMPLE MULTI ATTRIBUT RATING TECHNIQUE) - Romanus Damanik (Jurnal Informatika Kaputama (JIK), 2021)
Humans to be able to communicate with themselves and others are required to have the ability to read. Reading interest will grow if it is supported by adequate reading materials and is of interest to the reader, because it is from reading material that a person will encounter various things that have never been known before. The SMART method is a method for multi-attribute decision making. This multi-criteria decision-making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important it is compared to other criteria. This weighting is used to assess each alternative in order to obtain the best alternative. For that the writer tries to make a Decision Support System to Determine the Reading Interest of students in Borrowing Books. In making this Decision Support System the author uses MS. Visual Basic 2010 for data processing. Thus, a manual work process using the SMART method can be distinguished. From the calculation results of the 20 data that have been carried out, the ranking results with the highest score are Fahira Rambe (A7) with a value of 0.83, which means that they have the highest reading interest among other students.